Network performance evaluation of 6to4 tunneling - Bahaman, Nazrulazhar; Hamid, Erman; Prabuwono, Anton Satria (2012)
Several types of IPv6 transition mechanisms have been developed to facilitate the migration of IPv4 to the new protocol, IPv6. Although all transition mechanisms have the same objective, the process necessitates compliance with their respective capabilities. This paper focuses on the evaluation of the transition mechanisms namely 6to4 tunneling in terms of data transmission. The assessment is based upon experimental work that is conducted on a controlled environment. User-to-user network performance software is used to obtain the throughput, round trip time and tunneling overhead for TCP and UDP transmission protocol. The performance of TCP and UDP through 6to4 tunnel is then compared over the native IPv4 and IPv6 environment. As a result, the findings prove the ease of TCP data transmission via the tunnel compared to both native networks. In contrast, the UDP implementations show the slight difference for them. Â© 2012 IEEE.